Characterization of MXenes at every step, from their precursors to single flakes and assembled films. (July 2021) - Shekhirev, Mikhail; Shuck, Christopher E.; Sarycheva, Asia; Gogotsi, Yury
Abstract: The MXene field continues to grow and expand as more research groups begin to study this fascinating and very large class of 2D materials. While synthesis and applications of MXenes have been widely discussed in literature, characterization is often overlooked. Due to the large variety of MXene structures and compositions, it is often necessary to use multiple advanced characterization techniques within a single study, and each characterization technique has its own quirks, pitfalls, and benefits when applied to MXenes. This review focuses on the utilization of X-ray diffraction, X-ray photoelectron spectroscopy, Raman spectroscopy, electron microscopy/spectroscopy and a number of other techniques to understand if the precursor (MAX phase) is suitable for MXene synthesis, confirm successful synthesis of MXene, and finally determine its composition, structure and properties. Researchers should look to this review article as a guide to help them understand which techniques to use for characterization of their MXene samples and leverage the best characterization practices developed to date.